Empirical fear profiles among American youth - Schaefer, B.A.; Watkins, M.W.; Burnham, J.J. (Behaviour research and therapy, 2003)
Fears among children can range from relatively innocuous fears of simple objects to significant phobias that affect youths’ everyday functioning in the home, school, or community environments. This study investigated empirically derived fear profiles among American youth ages 7–19 ( N =556 ). Based upon youths’ scores on the 5 factors of the Fear Survey Schedule for Children—II (FSSC—II; Burnham & Gullone (Behav Res Ther, 35, 1997)), multistage Euclidean grouping was applied and produced 5 replicable fear cluster profiles with unique contours. Logistic regression odds ratios revealed specific associations of profile group membership with demographic characteristics such as child age, sex, and ethnicity.